THE CIVIC ENGAGEMENT AND RELIGIOUS HOSPITALITY IN OPEN DAG PPME AL IKHLASH AMSTERDAM - Muhammad Saiful Mujab (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
This article describes and analyses the Open dag event held by PPME Al Ikhlas Amsterdam. It is an annual event and a form of religious hospitality in which the members of PPME Al Ikhlas Amsterdam warmly welcome the guests or strangers. This study uses a perspective of hospitality from either scriptural or theoretical basis. In terms of scripture, religious hospitality is highly commended by Islamic and Christian scriptures. While in terms of theoretical perspective, there are many scholars who discussed the theme based on various approaches; theology, sociology, ethics. I found that Open Dag allows people from various backgrounds to meet in person and to become aquianted with the existence of PPME Al Ikhlas Amsterdam. The civic engagement which is gained through religious hospitality practiced by PPME Al Ikhlas Amsterdam leads to peace building among communities